Respostas
respondido por:
0
x² -4x - 5 = 0
Resposta: 5 e -1
√Δ = b² - 4ac
√Δ = (-4)² - 4*1*-5
√Δ = 16 + 20
√Δ = 36
√Δ = 6
x = ( -b +/- √Δ ) / 2a
x = ( -(-4) +/- 6) / 2
x' = 4 + 6 / 2
x' = 10 / 2
x' = 5
x'' = 4 - 6 / 2
x'' = -2 / 2
x'' = -1
Um abraço!.
Resposta: 5 e -1
√Δ = b² - 4ac
√Δ = (-4)² - 4*1*-5
√Δ = 16 + 20
√Δ = 36
√Δ = 6
x = ( -b +/- √Δ ) / 2a
x = ( -(-4) +/- 6) / 2
x' = 4 + 6 / 2
x' = 10 / 2
x' = 5
x'' = 4 - 6 / 2
x'' = -2 / 2
x'' = -1
Um abraço!.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás